Educación emocional y su incidencia en el aprendizaje académico de los estudiantes de básica media de la Unidad Educativa 23 de Junio del cantón Baba en el periodo 2024 - 2025 - Gorotiza Santillán, Joselin Kareli (2025)
Emotions are stimuli that the human being has, in other words, emotions are closely linked to the cognitive, the fact that a student shows joy, interest, curiosity helps to prolong the retention of information and to better understand the concepts. Considering it as an educational process, emotional education seeks to increase a good emotional state as a complement to the development of knowledge. Furthermore, emotional education should be considered as a main part of learning, that is, through its development, the student acquires skills for personality formation based on their knowledge, thus generating good self-esteem, better valuing, recognizing and externalizing their emotions so that when learning in the classroom, effective development occurs significantly. For this reason, the development of these emotional skills must be stimulated with activities directed by the competent authorities. These activities provide the teacher with the ability to generate good management of their emotions in their students. In this work, we aim to establish the relationship between emotions and the acquisition of learning. It also details academic learning and the mental processes that lead to developing significant knowledge for decision-making and problem-solving presented by students who attend sixth grade of basic education parallel C and D, through effective teaching that the teachers teach at the June 23 Educational Unit of the Baba canton.